Tingkat Ketergantungan Merokok dengan Persepsi Bahaya Merokok di Universitas X: Radya Rizky Dewi, Ferdy Muzzamil - Rizky Dewi, Radya; Muzzamil , Ferdy (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2024)
This study was conducted to examine the relationship between the level of smoking dependence and the perception of the dangers of smoking at X University. The subjects in this study amounted to 72 students with an age range of 18-24 years with sampling techniques using accidental sampling. The results of the hypothesis test using sperman rho with sig 0.017 > 0.05 indicate that there is a relationship between the level of smoking dependence and the perception of the dangers of smoking at X University. The conclusion of this study is that students already know the dangers of smoking for health but students find it difficult to quit smoking because of the addictive effect of cigarettes. Among the suggestions that can be given based on this research for further research is the need to add female respondents and expand the research location to better see how the level of smoking dependence with the perception of the dangers of smoking.